Literature and Historiography in the Spanish Golden Age The Poetics of History - Kluge, Sofie (Routledge Studies in Renaissance Literature and Culture, 2022)
Golden Age departures in historiography and theory of history in some ways prepared the ground for modern historical methods and ideas about historical factuality. At the same time, they fed into the period's own "aesthetic-historical culture" which amalgamated fact and fiction in ways modern historians would consider counterfactual: a culture where imaginative historical prose, poetry and drama self-consciously rivalled the accounts of royal chroniclers and the dispatches of diplomatic envoys; a culture dominated by a notion of truth in which skilful construction of the argument and exemplarity took precedence over factual accuracy. Literature and Historiography in the Spanish Golden Age: The Poetics of History investigates this grey area backdrop of modern ideas about history, delving into a variety of Golden Age aesthetic-historical works which cannot be satisfactorily described as either works of literature or works of historiography but which belong in between these later strictly separate categories.